Energy Performance of LDPC Scheme in Multi-Hop Wireless Sensor Network with Two base Stations Model - Younes El Assari; Mounir Arioua; Imad Ez-zazi; Ahmed El Oualkadi (Institute of Advanced Engineering and Science, 2017)
Conservation of the energy is one of the main design issues in wireless sensor networks. The limited battery power of each sensor node is a challenging task in deploying this type of network. The challenge is crucial in reliable wireless network when implementing efficient error correcting scheme with energy consuming routing protocol. In this work, we investigated the energy performance of LDPC code in multi-hop wireless sensor network. We proposed a model of two base stations to prolong the lifetime and build a reliable and energy-efficient network. Through performed MATLAB simulations, we examine the energy effectiveness of multiple base stations model on reliable wireless sensor network performance in different network dimensions.